The Influence of Brand Personality on Zara Customer Loyalty: A Survey of Zara Customers at Kota Kasablanka Mall (Oratio Directa, 2019)
This study examines the influence of brand personality on Zara customer loyalty at Kota Kasablanka Mall. It applies an explanatory quantitative approach using a survey method. The population comprised 8,931 customers, while 99 respondents were selected through non-probability sampling. Data were collected using questionnaires and analyzed with SPSS 19. The findings show a correlation coefficient of 0.827, indicating a strong relationship between brand personality and customer loyalty. The regression equation produced a constant of 12.928 and a positive regression coefficient of 0.600. The coefficient of determination was 0.685, meaning that brand personality explained 68.5% of customer loyalty, while the remaining 31.5% was influenced by other variables.
Keywords: Brand; Brand personality; Customer loyalty; Marketing communication; Zara